Pengaruh Pemberdayaan dan Profesionalisme Kerja Terhadap Motivasi serta Dampaknya pada Kinerja Guru SMK Negeri di Kabupaten Batu Bara - Hasudungan Siringoringo; Akrim Akrim; Indra Prasetia (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aimed to determine the effect of empowerment and work professionalism on motivation and its impact on the performance of State Vocational High School teachers in the Batu Bara district. This study uses a quantitative approach research design with a sample size of 217 people and data collection techniques using questionnaires and path analysis techniques. The study results show a direct and positive effect of empowerment on the teacher work motivation of 0.962 and an immediate effect of empowerment on teacher performance of 0.071. There is an indirect effect of empowerment on teacher performance of 0.0317. There is a direct effect of work professionalism on the motivation of 0.664 and an immediate effect of professionalism on teacher performance of 0.067. There is an indirect effect (impact) of work professionalism on teacher performance through work motivation of 0.044. In conclusion, these findings illustrate that simultaneously empowerment, teacher performance, and work professionalism influence the motivation of State Vocational Schools in Batu Bara District Key Word : Empowerment, Work Professionalism, Motivation. Performance of Teacher